Rhetorical Devices in Hillary Clinton Concession Speech - Maria Goldiana Taping; Yudi Juniardi; Dhafid Wahyu Utomo (Journal of English Language Studies, 2017)
After her losing in United States presidential election on November, 8th 2016, Hillary Clinton delivered an amazing and encouraging concession speech for all audiences around the world. One factor attributing to Hillary's success in a speech is that she has skillfully applied the variety of rhetorical devices. In accordance with this fact, this research tried to analyze the rhetorical devices and their respective function applied in the Hillary’s speech by using Harris’ theory. By watching the speech record and reading the transcription, the researchers collected the data. Then, to describe the phenomena qualitative research design was used in this research and textual analysis is used as a research method. Moreover, this research is kind of library research. The result shows there are thirteen rhetorical devices that were applied in the speech. Regarding to emphasis rhetorical devices, Hillary frequently used a sentential adverb, alliteration, anaphora, conduplicatio, diacope and epistrophe. For association rhetorical devices, Hillary utilized antanagoge, antithesis, metaphor, and parallelism. For decoration rhetorical devices, Hillary tended to apply asyndeton, polysyndeton, and sententia. Emphasis rhetorical devices are the most repeatedly used in her concession speech. Hillary used emphasis rhetorical devices to directly emphasize her point and purpose and also making the points of the speech is distinctly and explicitly delivered to the audiences. Keywords: rhetorical devices; Hillary Clinton Concession Speech; United States Presidential Election.